Maurice: Translating the Controversy, a Comparative Study of the English Text and its Spanish Version - Valdeón García, Roberto (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractThis article presents an overview of the literary controversy surrounding the publication of E. M. Forster’s so-called homosexual novel, Maurice, in 1971 and its subsequent publication in Spanish. Some critics published revisionist works in which his other novels were presented in the light of the revelations about Forster’s own homosexuality whereas others claimed that the novel shares some of the author’s major preoccupations as well as the literary themes and techniques present in all his narrative. Then we proceed to review some key concepts in Translation Studies necessary to carry out a comparative study of the text and the Spanish version: communicative translation, translators as cultural mediators, translation competence, factory translation. The study of the two texts covers three major areas: text level (including an analysis of grammatical features, lexicon, narrative style, conversational English), cultural level (studying key cultural concepts in the novel) and literary level (covering some of Forster’s key literary features, the notion of muddle, the anticipatory technique). We then proceed to study all these aspects at play in chapter 25, regarded as the turning point in the novel and as a key chapter both at discursive and literary levels. In the final section, we discuss the inadequacy of the choices made by the translators and the way in which they fail to offer the Spanish readership an adequate version both as regards the text per se and as part of Forster’s literary production, and we claim that it shares some of the characteristics of what Milton has called “factory translation.”